The Effect of The Electronic Mind Maps as A Pre and Post Graphic Organizer in The Development of Computational Concepts among Middle School Students - Almagedi, Muaadh Mohammed Hamid (Journal of Curriculum and Teaching Methodology, 2023)
Impact of the current research is to determine the effect of presenting electronic mind maps as a visual organizer (before- after) in developing computer concepts among middle school students in the first unit of the computer textbook entitled (I know my computer) and the second unit (I understand my computer), and the study sample was formed from three study groups of the first intermediate grade in Al- Mutassim Billah School affiliated to the education department in the eastern province, and they were randomly selected and divided into three groups, one of which was first experimental group, which reached (27) students, and the second experimental group reached (26) students and a control group. of reached (17) students. The researcher prepared an achievement test consisting of (20) questions, presented to a group of referees to ensure the validity of its content. it was applied to the study sample in determining the effect of the difference in presenting electronic mental maps as visual organizations (before- after) on developing computer concepts among middle school students. The results of the research reached a statistically significant difference at a significant level (α≤0.05) between the mean scores of the control group students and the first experimental group students in the post application of the achievement test of computational concepts due to the difference in the treatment method (the usual method- electronic mental maps as the post regulator) in favor of the first experimental group in the post application, and the presence of a statistically significant difference at the level of significance (α≤0.05) between the mean scores of the control group students and the students of the second experimental group in the post application of the achievement test of computer concepts due to the difference in the treatment method (the usual method- electronic mental maps as a regulator) (pre- application) in favor of the second experimental group in the post application, and the presence of a statistically significant difference at the level (α≤0.05) between the average scores of the students of the first experimental group (electronic mental maps as a post- organizer) and the average scores of the students of the second experimental group (electronic mental maps as a pre- organizer).
Keywords: Electronic Mind Maps; Computer Concepts; Visual Organizer (Before – After); Middle School